Peran Media Sosial dalam Pembentukan Identitas Budaya Mahasiswa di Kabupaten Semarang - Zalukhu, Eman Wardin; Yuliamir, Henry (Mahesa Research Center, 2025)
This study aims to thoroughly examine the role of social media in the formation of cultural identity among university students in Semarang Regency. Using a qualitative approach through a case study method, this research explores how students utilize social media as a medium to express, reinforce, and preserve their local cultural values, including traditions, regional languages, and cultural practices, while simultaneously interacting with influences from global cultures. The findings reveal that the majority of students actively use various social media platforms to showcase cultural content rooted in their regions, making social media not only a space for social communication but also a cultural negotiation arena. This process results in a hybrid cultural identity, a dynamic blend between authentic local values and adopted and adapted global cultural elements. Besides offering significant opportunities for digital cultural preservation and development, social media also presents challenges in the form of cultural value conflicts requiring adaptation skills, selective filtering, and critical reflection from students as cultural agents. The study recommends that students use social media wisely and critically to maintain the authenticity and sustainability of local culture, while educational and cultural institutions should actively support the innovative use of social media as a means to preserve and develop culture. These findings contribute important insights into the dynamics of cultural identity amid the evolving digital and globalized era.